Genetic and molecular characterization of type-IV glandular trichome development in tomato (Solanum lycopersicum cv. Micro-Tom) and its participation in arthropod resistance - Vendemiatti, Eloisa (2020)
Glandular trichomes are epidermal appendages capable of producing, storing, and releasing metabolites of economic and ecological importance that, among other functions, have a fundamental role in plant defense. The developmental path of these trichomes remains unclear since most of the studies involve the model plant Arabidopsis thaliana, in which multicellular trichomes are absent. The genus Solanum has a great diversity of trichomes, especially glandular types (I, IV, VI, and VII). Wild species such as S. galapagense and S. pennellii are sources of genetic resources for tomato (S. lycopersicum) because they have natural genetic variations that provide them with greater resistance to herbivore attacks. Among these variations, there is the presence of type-IV glandular trichomes, a source of acylsugar (AS), a multifunctional substance in the herbivores control. In this work, we sought to elucidate the genetic bases that control the development of type-IV glandular trichomes, in addition to understand the relationship of this structure with herbivory resistance. For this, two introgression lines were created in which the ability of both S. galapagense and S. pennellii to develop type-IV trichomes was introgressed into the cv. Micro-Tom. In the first chapter, we explored the Galapagos enhanced trichomes (MT-Get) line, which was produced from a crossing with S. galapagense. Although the lineage had a high density of type-IV trichomes, the plants remained susceptible to whitefly (Bemisia tabaci). Analysis of GC-MS, LC-MS, and gene expression showed that the presence of type-IV trichomes was not enough for AS high production. Furthermore, MT-Get mapping-by-sequencing revealed that five chromosomal regions containing S. galapagense alleles are associated with this phenotype. Thus, these results provide the basis for understanding the development of glandular trichomes, showing their polygenic nature in S. galapagense. Besides, they also subsidize the creation of insect-resistant tomatoes from varieties with a high density of type-IV trichomes, to be later complemented by pyramidization with the metabolic pathways associated with AS production. In the second chapter, the line Pennelli enhanced trichomes (MT-Pet) was obtained. In it, a single chromosomal region of S. pennellii is related to the presence of type-IV trichomes. The plants did not show any pleiotropic traits linked to the presence of type-IV trichomes, but GC-MS analyses and Rhodamine-B assay revealed a lack of AS. Although the type-IV trichome density in MT-Pet is much lower than in MT-Get, the monogenic trait of MT-Pet may facilitate the isolation of a critical ontogenic gene, thus helping to unravel the genetic basis for the formation of glandular trichomes, a development path that is still virtually unknown.